Dentists' soft skills: a scoping review - Anna Cândida Barsante Moreno Ortega; Débora Gonçalves Dupas do Nascimento; Antonio José Grande; Inara Pereira da Cunha (Springer, 2024)
Abstract Introduction Soft skills, essential for patient care, are relatively unfamiliar to dentists, necessitating investigation for the development of continuing education strategies. This study aimed to map the literature on soft skills usage in dental practice, based on dental professionals' perceptions, acknowledging the importance of conducting a scoping review to understand the current research landscape and identify areas needing attention from researchers and educators. Methods The research question was: "What are the soft skills investigated in dental practice?". Searches were conducted from November to December 2022 in the following electronic databases: virtual Health Library (BVS), National Library of Medicine (MEDLINE/PubMed), American Psychological Association (APA PsycNET), Scopus (Elsevier), and Portal Capes. Studies with dentists (public) who utilize soft skills (concept) in dental practice in both public and other settings (context), without language restrictions, between 2012 and 2022, were included. Results After applying the inclusion criteria, 266 articles were included. There was an increasing trend in publications over the last decade (R2 = 0.699). The non-public sector was the most addressed (60.15%). The dimension of intrapersonal skills was the most investigated (37.22%), followed by interpersonal skills (27.44%), communication skills (22.56%), professional ethical values (9.4%), and managerial skills (3.38%). Conclusion Research on soft skills in dental practice has surged in recent years, with a notable focus on intrapersonal skills. Nonetheless, the scarcity of literature on certain soft skills may impact the continuous education of professionals, highlighting the importance of stimulating further research in this area.